2017
DOI: 10.1161/atvbaha.117.309566
|View full text |Cite
|
Sign up to set email alerts
|

Circulating MicroRNA-125b Predicts the Presence and Progression of Uremic Vascular Calcification

Abstract: The results suggest that serum miR-125b levels are associated with VC severity and serve as a novel predictive marker for the risk of uremia-associated calcification progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 44 publications
0
56
0
Order By: Relevance
“…MiR‐125b is no exception in this perspective. During our systematic literature search, we identified 12 articles examining the diagnostic utility of miR‐125b in different types of cardiovascular diseases, with the first report published 5 years ago (Table ) . Among these diseases, we found that coronary artery disease/coronary events (n = 4) and acute stroke (n = 3) are the most common diseases in which the role of circulating miR‐125b has been investigated, followed by intracranial aneurysms (n = 2), abdominal aortic aneurysm (n = 1), heart failure (n = 1) and VC (n = 1) (Table ).…”
Section: Microrna‐125b: a Potential Biomarker For Vascular Diseasesmentioning
confidence: 99%
“…MiR‐125b is no exception in this perspective. During our systematic literature search, we identified 12 articles examining the diagnostic utility of miR‐125b in different types of cardiovascular diseases, with the first report published 5 years ago (Table ) . Among these diseases, we found that coronary artery disease/coronary events (n = 4) and acute stroke (n = 3) are the most common diseases in which the role of circulating miR‐125b has been investigated, followed by intracranial aneurysms (n = 2), abdominal aortic aneurysm (n = 1), heart failure (n = 1) and VC (n = 1) (Table ).…”
Section: Microrna‐125b: a Potential Biomarker For Vascular Diseasesmentioning
confidence: 99%
“…In vascular tissues, miR-125b over-expression leads to a lower degree of endothelial and VSMC proliferation, more vaso-relaxation, but a greater severity of inflammation, as summarized in a prior systematic review [83]. In terms of its effect on VC, the up-regulation of miR-125b is associated with less calcium deposition by murine and human VSMCs by directly repressing Ets-1 and osterix, an important osteoblastic marker [13,22]; furthermore, our previous work demonstrated that higher VC severity among uremic patients correlates with lower circulating miR-125b levels, supporting its anti-VC effect and its clinical applicability [33].…”
Section: Negative Vc-regulating Mirnasmentioning
confidence: 74%
“…Among these VC-related miRNAs, miR-125b is an important example; circulating miR-125b levels reportedly predict the clinical course of VC in patients with CKD. 4,5 Judging from the importance of miR-125b in vascular pathologies shown by a prior review 6 and its readiness for assay, measuring circulating miR-125b levels for vascular risk estimation may bear high clinical utility. However, determinants of circulating miR-125b levels remain unclear.…”
Section: Dear Editormentioning
confidence: 99%